The Role of Social Support on Resilience in People Living With HIV/AIDS : A Systematic Literature Review - Firman Firman; Sri Yona; Allenidekania Allenidekania (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2022)
During the COVID-19 pandemic, it had a fairly heavy psychological impact, so resilience or resilience was needed, especially for people with HIV/AIDS (PLWHA). This study is to determine the role of social support on resilience in people with HIV/AIDS. Resilience is a person's ability to adapt, survive and thrive in difficult situations. This study used a systematic literature review, which was carried out by means of a systematic review of several articles discussing social support and resilience in people with HIV/AIDS. Article criteria include international publication in English and full text. Article searches were carried out in February 2022 through 4 databases, namely PubMed, Wiley, Proquest, and Springer. Search using keyword ("PLWHA" AND "Social Support" OR "Perceived Social Supports" AND "Resilience" OR "Resiliences"). Articles were analyzed using JBI and Prisma tables. Based on the search for articles in the database, 217 articles were found, then selected through systematic stages so that eight selected journals were obtained. This systematic literature review found that social support was an important factor in increasing resilience in PLWHA. The most influential source of support was support from the family, namely: 30.4%, with (P=0.001). The perceived social support can reduce the impact of stress experienced. With high social support, it can reduce the use of harmful substances and increase ART adherence and contribute to improving the patient's health condition. In conclusion, perceived social support can play an important role, especially in increasing resilience, so it impacts the physical and psychological well-being of people living with HIV/AIDS.